Moral Education Values in the Dimensions of the Pancasila Student Profile Strengthening Project in the Merdeka Curriculum - Nurabiyah Nurabiyah; Mahariah Mahariah; Azizah Hanum (Dinasti International Journal of Education Management And Social Science, 2025)
This research is motivated by the need to integrate moral education values into the Pancasila Student Profile Strengthening Project (P5), as contemporary human life is increasingly distant from the fundamental values of Islam, namely the Qur'an and As-Sunnah. This study employs a qualitative research method with a library research approach. The researcher examines the document issued by the Curriculum and Assessment Standards Agency (BSKAP) No. 31/H/KR/2024, which outlines the competencies and themes of the Pancasila Student Profile Strengthening Project. The findings indicate that in the dimension of faith in God Almighty and noble character, the values of religiosity, honesty, responsibility, and humility serve as the foundation for shaping students' integrity and social awareness. In the dimension of global diversity, values such as tolerance, empathy, politeness, and humility play a crucial role in fostering harmonious relationships in a diverse society. Meanwhile, in the dimension of mutual cooperation, values of responsibility, generosity, environmental awareness, and discipline cultivate a sense of social duty and concern for others and the environment